The Pechenegs in the History of Turks - Saadettin GÖMEÇ (Ankara Üniversitesi Dil ve Tarih-Coğrafya Fakültesi Dergisi, 2017)
When we examine the Turkish history; Pechenegs who were one of the Turkish clans, could not establish a state structure, yet they at least became effective in the north of the Black Sea for a few centuries. Initially they struggled very hard with the Slavic-Russian and Byzantine Empire, and notably prevented them from arriving to the north of the Black Sea’s coasts for more than a century. The primary objective of this study is to summarize the history and the origin of Pechenegs, who unfortunately got a severe blow from their cognates, Cumans-Kipczaks.